2019
DOI: 10.1177/1687814019839906
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction and dynamic identification of driving intention adapting to multi-mode emotions

Abstract: Accurate identification of driving intention and reasonable control of driver's behavior is seen as an important mean to reduce man-made traffic accidents for the intelligent vehicle. However, the intention identification processes associated with driving emotion-related impact have received very little attention. With the aim of uncovering the emotional impact on driving intention identification, the car-following condition was taken as an example, and multi-source and dynamic data of human-vehicle-environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The acceleration pedal opening is regarded as the input of the neural network, and the experimental results indicated that the identification accuracy is greater than 95% during the first 600 ms with the proposed model. Wang et al 7 presented a feature extraction and dynamic identification model based on rough set theory and backpropagation artificial neural network to recognize the driver's intentions. The experimental results indicated that the identification accuracies of acceleration, maintaining speed, and deceleration were 80.33%, 76.58%, and 70.36%, respectively.…”
Section: Research Progress Of Starting Intention Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration pedal opening is regarded as the input of the neural network, and the experimental results indicated that the identification accuracy is greater than 95% during the first 600 ms with the proposed model. Wang et al 7 presented a feature extraction and dynamic identification model based on rough set theory and backpropagation artificial neural network to recognize the driver's intentions. The experimental results indicated that the identification accuracies of acceleration, maintaining speed, and deceleration were 80.33%, 76.58%, and 70.36%, respectively.…”
Section: Research Progress Of Starting Intention Identificationmentioning
confidence: 99%
“…According to the dataset established above, the sample form is the multi-dimensional time-series sample, which is converted into a three-dimensional array and read by the input layer in the model, as expressed in equation ( 6). The input in each time step is the sequence sample at the time t of one starting sample, as shown in equation (7). The length of the required input time step is 15.…”
Section: Establishment Of Starting Intention Identification Model Bas...mentioning
confidence: 99%
“…In order to reveal the influence of emotion on driving intention recognition, Xiao Yuan Wang obtained the multi-source dynamic data of human-vehicle-environment under the following conditions of different driving emotion states through emotion induction experiment and real vehicle experiment. The results showed that there were some differences in driving intention recognition under different emotion modes [4]. Klara Steinhauser and others conducted a driving simulator study.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks (NNs) are capable of learning the nonlinear characteristics inside a control object which is difficult to model in a deterministic manner. As such, NNs have been introduced to identify driving intentions in some special circumstances [22], [23]. In [24], the driver's starting intentions are defined as three modes, i.e., slow start, normal start and fast start, and the statistical law of the accelerator opening is set as the input of the back propagation NN (BPNN).…”
Section: Introductionmentioning
confidence: 99%